2007
DOI: 10.1093/ajcn/85.4.1050
|View full text |Cite
|
Sign up to set email alerts
|

Isoflavonoid glucosides are deconjugated and absorbed in the small intestine of human subjects with ileostomies

Abstract: Background:Although soy isoflavonoids have a number of healthpromoting benefits, information concerning the sites of their absorption and metabolism in humans remains limited. Isoflavonoid absorption from the gut requires deconjugation of glucosides to aglycones. Objective: The objective was to investigate the role of the small intestine in isoflavonoid absorption and metabolism in humans. Design: Human subjects with fully functional gastrointestinal tracts (n ҃ 6) and ileostomy subjects (n ҃ 6) were fed a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 39 publications
2
50
1
1
Order By: Relevance
“…We also have observed extensive small intestinal hydrolysis of IFN glucosides in human subjects with ileostomies [30]. Similarly, Walle et al [32] found that ingested quercetin glucosides were completely hydrolyzed to aglycones prior to absorption in human subjects with ileostomies.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…We also have observed extensive small intestinal hydrolysis of IFN glucosides in human subjects with ileostomies [30]. Similarly, Walle et al [32] found that ingested quercetin glucosides were completely hydrolyzed to aglycones prior to absorption in human subjects with ileostomies.…”
Section: Discussionsupporting
confidence: 63%
“…IFN and their metabolites were extracted from swine urine as previously described with slight modifications [29,30]. Aliquots of urine samples collected during the 24 h period before feeding the first test diet and 0 -24 and 24 -48 h after each test diet were separately analyzed to measure IFN equivalents excreted daily by each pig.…”
Section: Extraction Of Ifn and Their Derivatives From Swine Urinementioning
confidence: 99%
“…Absorption and metabolism of soy isoflavonoid glucosides have been extensively studied in recent years to elucidate their physiologic functions (Walsh et al, 2007;Islam et al, 2014). Deglycosylation by lactase-phloridzin hydrolase (LPH), an enterocyte-specific enzyme localized to the brush-border membrane in small intestine, is a critical step in the absorption and metabolism of isoflavonoid glucosides.…”
Section: Introductionmentioning
confidence: 99%
“…Deglycosylation by lactase-phloridzin hydrolase (LPH), an enterocyte-specific enzyme localized to the brush-border membrane in small intestine, is a critical step in the absorption and metabolism of isoflavonoid glucosides. This process generates aglycones that can enter enterocytes through passive diffusion (Day et al, 2000;Walsh et al, 2007). After cellular accumulation, aglycones undergo extensive metabolism in enterocytes (Chen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the inhibitory activities of these quercetin conjugates could be greater in the liver in vivo. The elimination half lives of quercetin metabolites in human studies were in the range of [10][11][12][13][14][15][16][17][18][19][20] hours. The relatively long half-lives of the quercetin conjugates imply that consumption of quercetin-rich foods can potentially inhibit hydroxycinnamic acid metabolism in vivo over a significant period of time (~1 day) [24].…”
Section: Discussionmentioning
confidence: 99%